Ascidia subterranea sp. nov. (Phlebobranchia: Ascidiidae), a new tunicate belonging to the A. sydneiensis Stimpson, 1855 group, found as burrow associate of Axiopsis serratifrons A. Milne-Edwards, 1873 (Decapoda: Axiidae) on Derawan Island, Indonesia - Kneer, Dominik; Monniot, Francoise; Stach, Thomas; Christianen, Marjolijn J. A. (Zootaxa, 2013)
A new tunicate, Ascidia subterranea sp. nov., was found in burrows of the axiid crustacean Axiopsis serratifrons on De-rawan Island, Indonesia. It differs from other ascidians in its habitat as well as numerous morphological peculiarities which are described in detail. The shrimp Rostronia stylirostris Holthuis, 1952 was found inside A. subterranea sp. nov., and 4 species of bivalves, 3 species of polychaetes, 1 gastropod, 1 polyplacophoran and 1 sponge species were found as burrow associates besides the ascidian.